Changes in patient‐perceived aggravating factors during the course of atopic dermatitis - Nozomi Yanagida; Ryo Saito; Akiko Kamegashira; Satoshi Morioke; Akio Tanaka (Frontiers Media S.A., 2023)
Abstract Objective This study aimed to clarify how patient‐perceived aggravating factors change during the course of AD. Methods This study involved a questionnaire‐based survey administered to 115 patients with AD at our hospital. The changes in patient‐perceived aggravating factors were examined as treatment progressed by readministering the questionnaire to 36 patients 6 months later. Results The most frequent aggravating factors at the first visit were sweating, emotional stress, and house dust. The number of patients who identified food, dust mites, house dust, pollen, and pets as aggravating factors decreased during the course of the disease. However, the number of patients who identified sweating, environmental factors, emotional stress, and lack of sleep as aggravating factors did not differ from those at the first visit; this included those who newly identified these as aggravating factors. Conclusion Many patients with AD are concerned about the aggravating factors, and it may be possible to reduce aggravating factor‐related anxiety by informing patients that certain aggravating factors may change during treatment. Hence, it is necessary to ask patients about the aggravating factors at the first visit and fixed intervals and resolve them immediately.